The Effect of Lung Cancer Prevention Education on Adolescent Smokers with Knowledge Deficits Using Audiovisual Media - Suryani, Dwi; Rahmawati Papuanidiharjo, Silva (Asy-Syifa : Journal of Science and Technology Nursing, 2025)
Purpose: Lung cancer is a malignant disease and remains one of the leading causes of death worldwide. One of the primary risk factors for lung cancer is smoking. Among adolescents, smoking habits are becoming increasingly common, influenced by peer pressure, media exposure, and lack of awareness about the health risks. This trend presents a significant challenge for healthcare providers, particularly nurses, to deliver effective health education aimed at lung cancer prevention. Enhancing adolescents' knowledge and awareness through appropriate health education methods is essential to encourage healthy behaviors and reduce the risk of lung cancer in the future. Method: This study utilized a descriptive research design with a case study approach. The subjects consisted of 32 students from SMPN 07 Cibitung who met the inclusion criteria: adolescents who had never received information regarding the dangers of smoking and who voluntarily agreed to participate in the study from beginning to end. Audiovisual media was used as the primary educational tool during the intervention. Results: The findings showed a notable improvement in the knowledge of the respondents after the health education was delivered. Of the 32 participants, 6 respondents (19%) achieved a moderate level of knowledge, while the majority—26 respondents (81%)—demonstrated a good level of knowledge regarding lung cancer prevention and the dangers of smoking. Conclusions: The results indicate that the use of audiovisual media in health education is effective in increasing adolescents' knowledge about lung cancer prevention. This method can be considered a valuable tool for nurses and educators in promoting healthy lifestyles and preventing smoking-related diseases among young people.